Answer:
hey bud its d
Step-by-step explanation:
the answer is B because it's B
Answer:
sometimes
Step-by-step explanation:
Let us assume the first number to be = x
Let us assume the second number to be = y
Then
x^2 - y^2 = 5
x^2 = y^2 + 5
And
3x^2 - 2y^2 = 19
Multiplying the first equation by -2, we get
- 2x^2 + 2y^2 = - 10
Now subtracting the two equations, we get
x^2 = 9
x = 3
Putting the value of "x" in the first equation, we get
(3)^2 - y^2 = 5
9 - y^2 = 5
y^2 = 4
y = 2
I hope that the procedure is clear enough for you to understand and this is the answer that you were looking for.
Answer: [C]: "<span> 8x</span>⁷<span> + 3x</span>⁶<span> + x</span>⁵<span> + 5x</span>⁴<span> − 2x</span>³<span> </span>" .
__________________________________________________